Gestão de capital de giro na internacionalização das empresas: uma análise comparativa entre empresas locais e multinacionais - Lee, Sin Eun (2016)
The aim of this research is to empirically test if the working capital management adopted by multinational companies can be altered in foreign market entries of complex countries like Brazil. Based on the results of a survey of 182 companies in the electro-electronics and machinery sectors in Brazil, tests were conducted to analyze the correlation between the decisions of companies to use factoring with psychic distance and elapsed time of operation in Brazil. Results led to a higher propensity in the use of factoring as an alternative tool for short-term financing by multinationals companies with a greater psychic distance and with less elapsed time of operation in Brazil. Research on international business suggest that greater psychic distance of multinationals companies increase the uncertainty and risks avoidance, thus leading to a higher demand in cash holdings. Depending on the elapsed time of operation in the foreign market, psychic distance can be shortened through a process of organizational learning